Examining the Cellular Transport Pathway of Fusogenic Quantum Dots Conjugated With Tat Peptide - Dai, Jie; Wang, Jun; Yang, Xuan; Xu, Zixing; Ruan, Gang (Frontiers in Bioengineering and Biotechnology, 2022)
Understanding the underlying transport mechanism of biological delivery is important for developing delivery technologies for pharmaceuticals, imaging agents, and nanomaterials. Recently reported by our group, SDots are a novel class of nanoparticle delivery systems with distinct biointerface features and excellent fusogenic capabilities (i.e., strong ability to interact with the hydrophobic portions of biomembranes). In this study, we investigate the cellular transport mechanism of SDots conjugated with Tat peptide (SDots-Tat) by live-cell spinning-disk confocal microscopy combined with molecular biology methods. Mechanistic studies were conducted on the following stages of cellular transport of SDots-Tat in HeLa cells: cellular entry, endosomal escape, nucleus entry, and intranuclear transport. A key finding is that, after escaping endosomes, SDots-Tat enter the cell nucleus via an importin β-independent pathway, bypassing the usual nucleus entry mechanism used by Tat. This finding implies a new approach to overcome the nucleus membrane barrier for designing biological delivery technologies.